Analysis of HCRTR2 Gene Variants and Cluster Headache in Sweden - Fourier, Carmen; Ran, Caroline; Steinberg, Anna; Sjöstrand, Christina; Waldenlind, Elisabet; Belin, Andrea Carmine (Headache, 2019)
Objective The purpose of this study was to investigate the HCRTR2 gene variants rs3122156, rs2653342, and rs2653349 in a large homogenous Swedish case‐control cohort in order to further evaluate the possible contribution of HCRTR2 to cluster headache. Background Cluster headache is a severe neurovascular disorder and the pathophysiology is not yet fully understood. Due to striking circadian and circannual patterns of this disease, the hypothalamus has been a research focus in cluster headache. Several studies with many different cohorts from Europe have investigated the hypocretin receptor 2 (HCRTR2) gene, which is expressed in the hypothalamus. In particular, one HCRTR2 single nucleotide polymorphism, rs2653349, has been subject to a number of genetic association studies on cluster headache, with conflicting results. Two other HCRTR2 gene variants, rs2653342 and rs2653349, have been reported to be linked to cluster headache in an Italian study. Methods We genotyped a total of 517 patients diagnosed with cluster headache and 581 controls, representing a general Swedish population, for rs3122156, rs2653342, and rs2653349 using quantitative real‐time PCR. Statistical analyses of genotype, allele, and haplotype frequencies for the 3 gene variants were performed comparing patients and controls. Results For rs3122156, the minor allele frequency in patients was 25.9% compared to 29.9% in controls (P = .0421). However, this significance did not hold after correction for multiple testing. The minor allele frequencies for rs2653342 (14.7% vs 14.7%) and rs2653349 (19.5% vs 18.8%) were similar for patients and controls. Furthermore, we found one haplotype that was significantly less common in patients than controls (P = .0264). This haplotype included the minor allele for rs3122156 and the major alleles for rs2653342 and rs2653349. Significance did not hold after applying a permutation test. Conclusions Our data show a trend for association between cluster headache and the HCRTR2 polymorphism rs3122156, where the minor allele seems to be a protective factor. However, the other 2 HCRTR2 gene variants, including the previously reported rs2653349, were not associated with cluster headache in our Swedish material. A comparison with previous studies points to variance in genotype and allele frequencies among the different populations, which most likely contributes to the opposing results regarding rs2653349. Although the results from this study do not strongly support an association, HCRTR2 remains an interesting candidate gene for involvement in the pathophysiology of cluster headache.